Nivolumab Versus Docetaxel for Previously Treated Advanced Non-Small Cell Lung Cancer in China: A Cost-Effectiveness Analysis - Liu, Qiao (Clin Drug Investig, 2019)
BACKGROUND AND OBJECTIVE: The economic assessment of immuno-oncology agents in Chinese patients is limited despite a need for new therapies. Nivolumab is the first immune checkpoint inhibitor approved for the second-line treatment of non-small cell lung cancer (NSCLC) in China, and it significantly prolongs overall survival. However, considering the high cost of nivolumab, it is urgent to assess its value in China in terms of both efficacy and cost. The objective of this study was to investigate the cost-effectiveness of nivolumab vs docetaxel in the second-line setting for NSCLC patients from the Chinese healthcare system perspective. METHODS: A Markov model consisting of three health states, was designed to evaluate the lifetime cost and effectiveness of nivolumab vs docetaxel in the second-line treatment of NSCLC patients. Clinical data was derived from the CheckMate 078 phase III clinical trial, which included 504 patients predominantly from China. Parametric survival models to fit and extrapolate survival data were chosen based on clinical rationality, visual fit and statistical goodness-of-fit. Lifetime costs and health outcomes were calculated, and US$28,899 and $63,564 per quality-adjusted life-year (QALY) were selected as the willingness-to-pay (WTP) threshold values for general regions and affluent regions, respectively. One-way and probabilistic sensitivity analyses were undertaken to explore the robustness of the model. Additional subgroup analyses were performed. RESULTS: In base case analysis, Nivolumab yielded an additional 0.24 QALYs, at a cost of $93,307 per QALY. Sensitivity analyses suggested that the results to be most sensitive to the price of nivolumab per kg (mean $60.00; range $26.00–$60.00) and the mean patient weight (65 kg, range 52–78 kg). Utility values in progression-free survival state (mean 0.804; range 0.643–0.965) and overall survival hazard ratio (0.68; 97.7% CI 0.52–0.90) had moderate impact on the model results. Subgroup analyses indicated that nivolumab was most cost-effective for patients who were 65 years of age or older ($85,171/QALY), followed by female patients ($85,273/QALY) and patients with tumor PD-L1 expression at least 1% ($90,309/QALY). CONCLUSIONS: Nivolumab is unlikely to be cost-effective compared with docetaxel for patients with previously treated advanced NSCLC in China. Ensuring that nivolumab is included in the National Reimbursement Drug List (NRDL) may be a valid mean of meeting extensive treatment demands in China. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s40261-019-00869-3) contains supplementary material, which is available to authorized users.